Supercapacitors: A Three‐Layer All‐In‐One Flexible Graphene Film Used as an Integrated Supercapacitor (Adv. Mater. Interfaces 11/2017). Issue 11 (9th June 2017) - Du, Jiamei; Zheng, Cheng; Lv, Wei; Deng, Yaqian; Pan, Zhengze; Kang, Feiyu; Yang, Quan‐Hong
Abstract : In article number1700004, Wei Lv, Quan‐Hong Yang, and co‐workers demonstrate an all‐in‐one graphene‐based flexible supercapacitor prepared by a step‐by‐step filtration followed by a selective photo‐reduction assisted with TiO2, where unreduced graphene oxide (GO) layers in the middle, act as the separator and the outside reduced GO‐TiO2 layers are used as active materials. This supercapacitor shows an extremely high volumetric energy density, excellent rate and cyclic performances together with a very good flexibility.